Aging: A revisited theory based on free radicals generated by NOX family NADPH oxidases - Krause, Karl-Heinz (Experimental gerontology, 2007)
Reactive oxygen species (ROS), often also referred to as free radicals, play an important role in aging. It is widely assumed that mitochondria are the predominant source of ROS relevant for the aging process. In this hypothesis article, we suggest that the role of ROS generated by NOX family NADPH oxidases has been largely overlooked in aging theories. NOX NADPH oxidases form a seven member gene family and are high level ROS-generating enzymes. As opposed to mitochondria, which generate ROS as a byproduct of their metabolism, NOX enzymes are professional ROS generators. From an experimental point of view, there is now abundant evidence for the involvement of NOX enzymes in age-associated diseases. The role of NOX enzymes in the aging process itself and their relative contribution as compared to mitochondria needs further investigations.